Pengaruh Return On Asset dan Debt To Asset Ratio Terhadap Audit Delay - Murdan Sianturi; Revika Verawati Simbolon (Mulia Pratama, 2023)
The aim of this research is to determine the effect of return on assets and debt to asset ratio on audit delay in food and beverage sub-sector companies listed on the IDX for the 2020-2022 period. This research uses secondary data which can be accessed via the Indonesia Stock Exchange website (www.idx.co.id) in the form of financial reports and company annual reports. The data analysis techniques used are the classic assumption test, t test, F test and multiple regression analysis using Eviews software. The research results show that first, ROA has a significant effect on audit delay. This is indicated by the value of tcount < ttable (-1.8166 > 1.671) with a prob value of 0.0473 < 0.05. Second, DAR has no significant effect on audit delay. This is indicated by the value of tcount > ttable (0.5227 < 1.671) with a prob value of 0.6031 > 0.05. Third, ROA and DAR simultaneously have a significant effect on audit delay. This is indicated by the value of Fcount > Ftable (3.7503 > 3.150) and a significance value of 0.02 < 0.05.